Morphing applications in automobiles: a review. (17th August 2021) - Anumodh, R.; Singh, Balbir; Zuber, Mohammad
Morphing structures are structures that alter their shape and size upon application of a stimulus. This field has been of interest to numerous researchers all over the world due to its advantages over conventionally used materials. Most reported morphing studies are confined to aerospace applications and studies conducted specifically for automotive applications are limited. This paper discusses morphing technology applications in automobiles particularly with popularly used smart materials like Shape Memory Polymer, Shape Memory Alloy, Elastomers, and others. It also addresses systems such as sensors and actuators required for morphing structures to function. Some morphing applications in an automobile have been covered. Some research in the morphing of aerostructures can be incorporated into the automotive industry, so an attempt is made to correlate the findings of aerospace research to potential automotive applications.